POTENSI PARIWISATA RIAM SEBULUH DI KOTA BENGKAYANG DALAM MENINGKATKAN EKONOMI MASYARAKAT - Sabinus Beni; Blasius Manggu; Yeremia Niaga Atlantika; Usman (JURNAL BORNEO AKCAYA, 2022)
The research aimed to find out the structuring activities that have been carried out and the planned activities to be carried out by the local government and landowners in maximizing the potentials of tourism in the City Center of Bengkayang, Bengkayang Regency. It was a descriptive, qualitative study. The present research was conducted in the Sebalo Village, Bengkayang District. The data were collected through direct visits to the field and in-depth interviews with the key informants, the landowners, the surrounding communities, and the local governments. The result of the study showed that there had been no arrangement activities at the locations around Riam Sebuluh. The intervention of the local government was not identified as an effort to preserve the environment of Riam Sebuluh located in the centre of Bengkayang City. The local government did not concern the importance of protecting the environment from the pollution of the Sebalo River in Bumi Emas Village, Bengkayang District, where the water was previously clear and became the pride of the Bengkayang people, and are now turning into very dirty. This condition needs to get the attention of all parties, especially the local government, through the policy interventions so that the community remains and obeys in maintaining the environment by not polluting the watershed through waste disposal or gold mining without a permit.